Qualitative research methods/Monique Hennink, Inge Hutter, Ajay Bailey. - Hennink, Monique, author (SAGE Publications Ltd., 2020)
"Practical and straightforward, this book is a multidisciplinary introduction to the process of planning, conducting and analyzing qualitative research, from selecting appropriate methods to publishing your findings. Built around the authors' Qualitative Research Cycle - consisting of the design, data collection and analytic cycles - this pragmatic guide clearly demonstrates the steps you need to take to ensure your research is rigorous and robust. Constructed from the authors' decades of experience teaching workshops, the book is packed with techniques and tools to help you turn theory and method into research practice. This second edition: - Showcases the importance of linking research design to data analysis, helping you avoid potential pitfalls and get the most out of your data - Highlights the relevance and wide application of qualitative methods with an array of international examples of real field research and interdisciplinary case studies - Gives clear guidance on writing qualitative research, including how to respond to critiques of qualitative methods - Has a renewed focus on evaluating quality in qualitative research, ensuring your work is valid, reflexive and ethical Offering tried and tested research tools like interview guides that you can apply to your own projects and supported by online resources including checklists and reflective questions, this book is the perfect companion for anyone looking to complete a successful project using qualitative research methods"--